2021
DOI: 10.15218/zjms.2021.030
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with scabies in Erbil, Iraq

Abstract: Background and objective: Scabies, known as the seven-year itch, is a contagious skin infestation by the mite Sarcoptes scabiei that causes a pruritic skin eruption. Scabies is endemic in most of the communities of the developing world. This study aimed to assess the quality of life of scabies patients, taking into consideration the demographic profile and clinical presentation of patients in Erbil. Methods: In this cross-sectional study, 107 scabies patients attending a private dermatology clinic were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The mean DLQI score of our study population was 13.16±7.638. This value was in concordance with the previous studies of DLQI in scabies, which reported mean DLQI values of between 10.09 and 14.95±4.5 [ 1 , 17 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The mean DLQI score of our study population was 13.16±7.638. This value was in concordance with the previous studies of DLQI in scabies, which reported mean DLQI values of between 10.09 and 14.95±4.5 [ 1 , 17 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, in one study, DLQI in 72.2% of patients was moderate-to-extremely affected. DLQI was ‘affected severely’ in 41.3% (n=38) of our patients, similar to most of the previous studies [ 1 , 17 ]. A mild effect was reported only in one study performed in rural areas, and the authors concluded that this may be attributable to the fact that the QoL is so poor that people do not consider scabies as a problem at all [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations